CXCR4 Antagonist TG-0054 Mobilizes Mesenchymal Stem Cells, Attenuates Inflammation, and Preserves Cardiac Systolic Function in a Porcine Model of Myocardial Infarction. Issue 7 (July 2015) - Hsu, Wan-Tseng; Jui, Hsiang-Yiang; Huang, Ying-Huey; Su, Mao-Yuan M.; Wu, Yen-Wen; Tseng, Wen-Yih I.; Hsu, Ming-Chu; Chiang, Bor-Luen; Wu, Kenneth K.; Lee, Chii-Ming
Interaction between chemokine stromal cell-derived factor 1 and the CXC chemokine receptor 4 (CXCR4) governs the sequestration and mobilization of bone marrow stem cells. We investigated the therapeutic potential of TG-0054, a novel CXCR4 antagonist, in attenuating cardiac dysfunction after myocardial infarction (MI). In miniature pigs (minipigs), TG-0054 mobilized CD34 + CXCR4 +, CD133 + CXCR4 +, and CD271 + CXCR4 + cells into peripheral circulation. After isolation and expansion, TG-0054-mobilized CD271 + cells were proved to be mesenchymal stem cells (designated CD271-MSCs) since they had trilineage differentiation potential, surface markers of MSCs, and immunosuppressive effects on allogeneic lymphocyte proliferation. MI was induced in 22 minipigs using balloon occlusion of the left anterior descending coronary artery, followed by intravenous injections of 2.85 mg/kg of TG-0054 or saline at 3 days and 7 days post-MI. Serial MRI analyses revealed that TG-0054 treatment prevented left ventricular (LV) dysfunction at 12 weeks after MI (change of LV ejection fraction from baseline, −1.0 ± 6.2% in the TG-0054 group versus −7.9 ± 5.8% in the controls). The preserved cardiac function was accompanied by a significant decrease in the myocardial expression of TNF-α, IL-1β, and IL-6 at 7 days post-MI. Moreover, the plasma levels of TNF-α, IL-1β, and IL-6 were persistently suppressed by the TG-0054 treatment. Infusion of TG-0054-mobilized CD271-MSCs reduced both myocardial and plasma cytokine levels in a pattern, which is temporally correlated with TG-0054 treatment. This study demonstrated that TG-0054 improves the impaired LV contractility following MI, at least in part, by mobilizing MSCs to attenuate the postinfarction inflammation. This insight may facilitate exploring novel stem cell-based therapy for treating post-MI heart failure.